The necessity for a guideline in selection of marriage partners based on the concept of compatibility (kafa’ah) - Mohd Kusrin, Zuliza; Nazir Alias, Muhammad; Abdul Majid, Latifah; Yusuf, Wafaa’ (2023)
Every person desiring to establish a family will have a certain preference of criteria for their potential spouse. Islam has outlined guidelines for choosing a marital partner through the concept of compatibility (kafa'ah), based on the hadith of the Prophet Muhammad (peace be upon him), which provides four fundamental criteria: religion, lineage, health, and beauty. Furthermore, classical and contemporary scholars have expanded from these basic criteria of compatibility (kafa'ah) to include some other criteria based on local societal norms. In line with the concept of Malaysia Madani, which is founded on fostering a Madani society, the establishment of families guided by the principles of compatibility (kafa'ah) is believed to enable individuals to achieve well-being and happiness in marriage. This article aims to discuss the concept of compatibility (kafa'ah), the discussion related to the criteria of kafa'ah, and the justification for the need to establish guidelines for the selection of marriage partners based on the concept of compatibility (kafa'ah). The research methodology employed document analysis and partial and structured interviews with eight informants, including muftis, scholars, shariah court judges, shariah lawyers, family counselors, and academicians in the field of family and Islamic jurisprudence (fiqh). Qualitative analysis of the interview data was conducted using Atlas.Ti software. The results of the interviews with informants revealed the necessity of proposing guidelines for the selection of marriage partners based on compatibility (kafa'ah) as one of the mechanisms to encourage society to achieve well-being and happiness in marriage in accordance with the maqasid shariah (objectives of Islamic law). The implications of the study also suggest the need to establish guidelines for compatibility (kafa'ah) criteria as a practical guide for shariah courts and Islamic religious offices at the state level when dealing with compatibility (kafa'ah) related issues.